Prioritising Rural development in 8th five year plan
According to the author the thrust of the Eighth Plan is remarkably set on bringing up panchayats - democratic representative institutions at the village level for giving a new meaning and new life to development as a whole. The author further describes that the plan decument, endorsed by the NDC at its 23rd December, 1991 meeting, has argued in favour of micro-planning or area planning by people' institutions as the only effective strategy for overpowering some of our most for midable challenges.
Keywords: Village Panchayats; Rural Development; Panchayati Raj; Eight Five Year Plan; Rural Development - India